Optimalisasi Mutu Sensori Produk Stik Cumi (Sthenoteuthis oualaniensis) Olahan Kelompok Nelayan Desa Motto, Kota Bitung, dalam Pengembangan Ekonomi Lokal - Ndahawali, Daniel Heintje; Wewengkang, Itje Danti; Ticoalu, Fidel; Soeharso, Agusta Putri Balqis Linda; Hariyoto, Fitroh Dwi (Politeknik Kelautan dan Perikanan Bitung, 2023)
One of the non-fish catches scattered in Bitung City is squid. The squid of the Sthenoteuthis oualaniensis type that are caught by fishermen from Motto Village, Bitung City, which is also processed by a group of fishermen as a processed product of squid sticks. Processed squid stick products have not been standardized both in terms of recipe and process. Therefore it is necessary to optimize squid stick products in the context of local economic development. This research aims to obtain optimal squid stick products in salt addition based on consumer acceptance. The hedonic test results obtained showed that the addition of 10% salt by weight of the raw material for squid, which fried for 45 seconds at ± 1200 C was the most preferred composition. Jurnal Bluefin Fisheries, 5 (1), 37 This salt composition can be used as a reference for standard recipes for the manufacture of subsequent products, with the process flow that are the preparation of raw squid ingredients, preparation of additional ingredients (dough and seasoning ingredients), mixing of ingredients, kneading, making the stick form, frying and packaging. Recipe standards that can be submitted as references based on this research are 100% raw squid, 280% flour, 40% sugar, 10% salt, 60% garlic, 1% ginger, 10% butter, 1 egg, and 1% emulsifier (from total weight of material).